The "Plan" phase of a Deming cycle: Measurement of quality and outcome of root canal treatments in a university hospital. (7th October 2018) - Cousson, Pierre‐Yves; Decerle, Nicolas; Munoz‐Sanchez, Marie‐Laure; Roux, Dominique; Doméjean, Sophie; Nicolas, Emmanuel; Hennequin, Martine
Abstract: Introduction: In many countries, dental students are taught in private or university hospitals where they treat patients under the supervision of teachers. Assessing the quality of root canal treatments (RCT) would provide information about the quality of care patients receive when treated by students. Methods: This study describes the six‐step "Plan" phase of a Plan‐Do‐Check‐Act (PDCA) cycle that identifies and analyses clinical practices in endodontics in a university dental hospital service. Results: Step 3 reported that the proportion of RCTs of adequate quality reached 57.1% and this proportion was significantly decreased when specific indicators for treatment difficulties were present. The proportion of successful RCTs after 1 year was 65.6%, and its variation was influenced by the preoperative periapical status rather than the quality of RCTs. The consensual meeting in Step 6 proposed to introduce three new procedures for the further Do, Check and Act phases of the PDCA cycle. Conclusion: This study encourages systematic evaluation of RCTs and provides the first step of the methodology that can be reproduced in private and hospital practices where students are asked to treat patients.